Synthesis of a Novel X-Type Chromophore with Two Imidazole Groups Under Microwave Irradiation - Kong, Fanpeng; Liu, Qingjian; Wu, Xue (Asian Journal of Chemistry, 2011)
A novel series of asymmetric X-type chromophore, which bears two imidazole groups, were designed and synthesized in two steps at high yields under microwave irradiation. All of the chromophores were characterized by 1H NMR and IR spectra. The organic compound shows better thermal stability due to the molecular structure introduced by the imidazole heterocyle.